E-LEARNING EQUIPMENT IN LEARNING PROCESSAT VOCATIONAL HIGH SCHOOL - Arif Wahyu Wirawan; Wahyudi Wahyudi (Universitas Sebelas Maret, 2018)
The problem in the world of education at this time is the quality and quantity of education in the field of information and communication technology. The quality of education can be seen from the quality of education desired by the community and for the quality of education related to the equitable access to education without any gap. One way to overcome these problems is by optimizing the role of information and communication technology in the learning process by using e-learning. E-learning used is using online learning based on Schoology. In this application there are several features that can be used by the teacher in the learning process including uploading material, assignments, discussions and giving test questions using the online quiz system. In the use of E-Learning in the learning process can increase students' learning motivation and can create enjoyable learning so that students in participating in learning activities can be active and achieve maximum learning outcomes.